Powers of investigator in proving on criminal cases for draft of the new Criminal Procedure Code of the Republic of Kazakhstan. (Journal of actual problems of jurisprudence, 2016)
This paper is devoted to the scientific authority of the investigator in proving criminal cases on the draft of the new CPC. Research material described below can be used successfully in the educational pro- cess of legal education, training institutes, in -service training system. The material can be used in working through the legal acts regulating the organization and tactics of search operations in connection with the introduction of the institute undercover investigation. In connection with the new edition of the Criminal Code, the Criminal Procedure Code, the UIC and the Administrative Code, the statutory ordinances Sun, monitored the study. The material research can be successfully used in the development of programs and schedules for mass retraining of practical law enforcement officials.
Keywords: The Constitution; the message of the law; the investigation; criminal procedure